Insights into the protective effect of omega-3 nanoemulsion against colistin-induced nephrotoxicity in experimental rats: regulation of autophagy and necroptosis via AMPK/mTOR and RIPK1/RIPK3/MLKL signaling pathways - Medhat Taha; Omer Abdelbagi; Tourki A. S. Baokbah; Rehab M. Bagadood; Naif A. Jalal; Rami Obaid; Nawal E. Al-Hazmi; Naeem F. Qusty (Renal Failure)
Colistin is considered one of the most effective antibiotics against gram-negative bacteria. However, nephrotoxicity is one of the dose-limiting factors in its treatment. This study aimed to evaluate the outcome of omega-3 nanoemulsion against colistin-induced nephrotoxicity and its possible underlying mechanism. Four rat groups were involved in the present research; each group containing ten rats was divided as follows: Group I (control) rats received normal saline; Group II (omega-3 nanoemulsion) rats received a dose of 500 mg/kg/body weight orally; Group III (colistin) rats received colistin intraperitoneally (300.000 IU/kg/day); and Group IV (colistin/omega-3 nanoemulsion) rats were treated for six days. The results revealed that colistin administration caused deterioration in renal functions such as creatinine, blood urea nitrogen, 24 h proteinuria, and kidney injury molecule-1 with decrease in creatinine clearance, resulting in histological alternation and tubular damage with diffuse interstitial inflammation. Additionally, colistin significantly increased the lipid peroxidation marker malonaldehyde, proinflammatory cytokines tumor necrosis alpha, interleukin-6, interleukin-1 beta. Also, autophagy influx marker microtubule-associated protein light chain 3B, Beclin-1, and necroptotic related proteins, receptor-interacting protein kinase-3 (RIPK-3), RIPK-1, mixed lineage kinase domain-like protein, and autophagy pathway regulatory kinase AMP-activated protein kinase, with a decrease in antioxidant enzymes catalase, superoxide dismutase, and total antioxidant capacity, autophagic marker ubiquitin-binding protein (p62), and regulator Mammalian target of rapamycin. Interestingly, omega-3 nanoemulsion reversed the results above, dramatically improving renal function and histological picture. Thus, omega-3 nanoemulsion provided a notable method for suppressing colistin-induced nephrotoxicity via its antioxidant and anti-inflammatory power, inhibiting pathological autophagy and necroptosis.